Tilapia marketing network of small-scale aquacultirist in Oaxaca, Mexico (Agro Productividad, 2025)
Objective: To identify and describe the type of short food supply chains (SFSC) in the tilapia marketing network´s core localities, where the small-scale aquaculturists (SSA) carry out their activity. Design/methodology/approach: An instrument was designed to be applied to the main head of the production unit, based on the conceptual framework of SFSC. The information was coded, and network analysis (NA) was performed.Results: The SFSC are the primary method of marketing of the SSA; we identified, according to the conceptual framework, six types of short supply chains: Farm-selling, local markets, point of sale, delivery, consumption on the production site, and one intermediary. The core localities of the tilapia marketing network have the highest values in degree and betweenness and were identified as articulation points, due to the relations of purchase-sale at local level and the interaction with actors of other localities.Limitations on study/implications: The work was developed only with SSA registered by the Oaxacan Aquaculture Committee of Health and Safety.Findings/conclusions: The isolated SMA develops SFSC at local level, while the SMA located in better-linked regions constructs mixed purchase and sale relationships from other locations. It was identifying a regional network of tilapia marketing, specifically related to Veracruz state.